Changes in obesity and BMI among children and adolescents with selected chronic conditions during the COVID‐19 pandemic. Issue 10 (30th August 2022) - Rifas‐Shiman, Sheryl L.; Aris, Izzuddin M.; Bailey, Charles; Daley, Matthew F.; Heerman, William J.; Janicke, David M.; Lin, Pi‐I Debby; Petimar, Joshua; Block, Jason P.
Abstract: Objective: The aim of this study was to examine COVID‐19 pandemic‐related changes in obesity and BMI among patients aged 5 to <20 years with selected chronic conditions. Methods: A longitudinal study in 293, 341 patients aged 5 to <20 years who were prescribed one of five medication classes (for depression, psychosis, hypertension, diabetes, or epilepsy) and who had BMI measures from January 2019 to March 2021 was conducted. Generalized estimating equations and linear mixed‐effects models were used, accounting for within‐child repeated measures and stratified by age, race, ethnicity, gender, and class of medication prescribed, to compare obesity and BMI z score during the pandemic (June through December 2020) versus pre‐pandemic (June through December 2019). Results: Obesity prevalence increased from 23.8% before the pandemic to 25.5% during the pandemic; mean (SD) BMI z score increased from 0.62 (1.26) to 0.65 (1.29). Obesity prevalence during the pandemic increased at a faster rate compared with pre‐pandemic among children aged 5 to <13 years (0.27% per month; 95% CI: 0.11%‐0.44%) and 13 to <18 years (0.24% per month; 95% CI: 0.09%‐0.40%), with the largest increases among children aged 5 to <13 years who were male (0.42% per month), Black (0.35% per month), or Hispanic (0.59% per month) or who were prescribed antihypertensives (0.28% per month). Conclusions: The COVID‐19 pandemic has exacerbated the obesity epidemic and widened disparities among children with selected chronic conditions. These findings highlight the importance of continuing efforts to specifically help high‐risk populations who are experiencing weight gain from the pandemic.